Exploration of The Relationship Between Entrepreneurship Education and Product Innovation in The MSME Environtment - Siswati, Aris; Suryo Parkoso, R. Agung; Purnami Restu Suwondo, Juwita (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2024)
This study examines the impact of entrepreneurial education level, business capital, business age, and workforce size on product innovation in SMEs in Malang City. Data were collected via questionnaires and analyzed using Partial Least Squares (PLS). Results indicate that all four variables positively and significantly affect product innovation. Entrepreneurial education, particularly technical skills and managerial abilities, provides a crucial foundation for innovation. Business capital, especially initial capital, supports innovation implementation, while business age shows that experience enhances SMEs' innovative capacity. Workforce size, particularly permanent employees, plays a vital role in innovation stability. The moderating effects of business capital, business age, and workforce size strengthen the relationship between entrepreneurial education and product innovation. Recommendations include improving access to capital, entrepreneurship training, and workforce stability support to enhance SMEs’ product innovation.